OPTIMIZATION OF CONTINUOUS ETHANOL PRODUCTION FROM SPENT BLACK TEA HYDROLYSATE USING IMMOBILISED ESCHERICHIA COLI KO11 - Kalender, Mehmet; Altundogan, Hamdi Soner (Editura Acad Romane, 2025)
Spent black tea waste (SBTW) was subjected to acid and then enzymatic hydrolyses. Fermentation experiments were carried out in a continuous fermentation system (CFS) and were optimized by RSM. Independent variables in RSM were as follows: reduced sugar concentration, flow rate, temperature, and immobilised cell fill ratio. The response variable was bioethanol yield. The SBTW hydrolysate was composed of fermentable sugars, such as glucose, xylose, galactose, and arabinose. It was determined that the significant single parameters in the developed model were reduced sugar concentration and flow rate. A bioethanol yield above 90% was achieved at the optimal point and this yield value continued steadily for 192 h. The dilution rate, hydraulic retention time, productivity, CO2%, and pH range at the optimal point were 0.300 h(-1), 3.333 h, 41.698 g/L day, 81.40%, and 5.81-6.5, respectively. The outer surface of the beads, with an average diameter of 1.871 mm, was smooth, and the E. coli KO11 cells on the inner surface of the beads were rod-shaped, as typical of these bacteria.
Keywords: continuous bioethanol production; spent black tea; acidic and enzymatic hydrolysis; immobilised E. coli KO11; optimization